The Level of Public Knowledge About Dagusibu Medicine in Rw 09, Padasuka Village, Cimenyan District, Bandung Regency - Eva Kusumahati; Tiara Anisa; Pegi Sugiartini (Journal of Social Research, 2023)
DAGUSIBU (Get, Use, Store and Discard) Medicine is a health education program created by the Association of Indonesian Pharmacists (IAI) which is useful for realizing the Movement Drug Awareness Family. The DAGUSIBU program aims to increase public knowledge regarding medicine. More precisely, the slogan invites the public to get, use, store and dispose of drugs in the right way. The purpose of this study was to determine the level of knowledge of DAGUSIBU drug in the community RW 09 Padasuka Village, Cimenyan District, Bandung Regency. This type of research is an analytic observational study with a design cross-sectional. The subjects were selected by Nonprobability Sampling (not random) as many as 95 residents of RW 09 who were the sample resproperly store and dispose of drugslling out a knowledge questionnaire about DAGUSIBU. The data obtained were categorical ordinal data which were analyzed using Microsoft Excel. Based on the results of the research obtained with different characteristics, including by gender, age, level latest education, and occupation, the community of RW 09 Padasuka Village, Cimenyan District, has a knowledge level of DAGUSIBU medicine with a less category of 28.42%, enough of 51.58 % and good at 20.00%. Conclusion: The results of the analysis showed that most of the level of knowledge of the residents of RW 09 Padasuka Village was sufficient with a percentage of 51.58%.